Virtual machine placement method for energy saving in cloud computing - Pragan Wattanasomboon (2018)
© 2015 IEEE. Nowadays, cloud computing has been widely used. The Virtual Machines (VMs) are created on servers in cloud computing. The VM scheduling on servers for energy saving in the cloud computing has been studied. The Virtual Machine Scheduling Algorithm (VSA) is proposed to schedule VMs in cluster environments. However, it is not effective and has high time complexity. In this paper, we propose a new scheduling method called Energy-aware Virtual Machine Placement (EVP) method to schedule VMs that can reduce power consumption. In addition, the EVP method has lower time complexity. We also formulate power consumption model to evaluate the performance of the EVP method. Finally, we evaluate the EVP method by simulation. The experimental results show that the EVP method has better performance.